THE INFLUENCE OF WORK COMPETENCE ON WORK PRODUCTIVITY WITH WORK MOTIVATION AS A MODERATING VARIABLE - Mardiani, Eri; Haryaka, Usfandi; Aziza, Failasufa; Salabi, Ahmad; Setiawan Wibowo, Teguh (ITB AAS Indonesia Surakarta, 2024)
Abstract Researchers believe that the Work Competence variable can have a positive relationship and a significant influence on the Work Productivity variable. Different from previous studies, this research adds the Work Motivation variable which researchers believe can moderate the influence of Work Competence variables on Work Productivity. This research is quantitative research with an explanatory approach. This research data was obtained using a questionnaire method distributed to 250 Bank Mandiri employees spread throughout Indonesia with the criteria of having worked for a minimum of 2 years. This data can be called primary data. The data was analyzed using the smart PLS 4.0 method. The results of this research show that the Work Competence variable has a positive relationship and has a significant influence on Work Productivity because the better the Work Competency, the more qualified the workers are, so that the work carried out will be more effective, efficient, and the target will be easier to achieve. Apart from that, the Work Motivation variable can moderate the influence of the Work Competency variable on Work Productivity because the better the employee's motivation, the more enthusiastic the employee will be so that it can go hand in hand with Work Competency which will ultimately have a more significant influence on Work Productivity. Keywords : Work Motivation, Work Competence, Work Productivity